The implementation of a performance management system in the Northern Cape Department of Environment and Nature Conservation - Mbanjwa, Sibonelo Glenton (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
This document consists of three sections, and they are the academic paper (section 1), literature review (section 2) and research methodology (section 3). The academic paper consists of the purpose of the research, the summarised literature review, summarised research methodology and the research findings. The literature review section is a detailed review of literature used in this study. The research methodology section explains the research methodology and design which was employed in this study and it gives more details than the summarised version of the academic paper section. This summary integrated all the elements of section 1, section 2 and section 3. The purpose of this research is to identify the main problems that the Department of Environment and Nature Conservation (DENC) could encounter during the implementation and use of a performance management system, based on employee perspectives. The objectives of this research are therefore: to establish how often a particular problem has been encountered during the implementation and use of a performance management system in DENC; to identify the impact of various problems on the implementation of a performance management system, to establish whether these problems can be easily solved or not, and to analyse the problems associated with the implementation of a performance management system, as well as making recommendations for the successful implementation of a performance management system in the future. In this study, the researcher employed both quantitative and qualitative research approaches, informed by post-positivism as research orientation. The data collection techniques employed in this research include survey questionnaires and individual interviews. The survey questionnaire was answered by fifty respondents, and interview questions were answered by four respondents. The ethical issues were addressed by writing a letter to the Head of Department and getting authorisation to complete the research and informing respondents of their right to withdraw and to participate voluntarily. The findings indicate that the problems are either sometimes encountered or rarely encountered, and the division is about fifty percent of those sometimes encountered to those rarely encountered. This research indicates that most of the problems have a moderate impact on the use and implementation of a performance management system. The lack of management has a high impact, and a lack of positive attitude to performance management system (PMS) certainly has an impact on the use and implementation of the performance management system. Items such as the problem of information and communication technology (ICT) which does not support PMS adequately, and defining too many key performance indicators (KPI), have a small impact on the use and implementation of the performance management system. There are three problems which are difficult to solve and they are: lack of management commitment, organisational members"Ÿ lack of positive attitude to the PMS and an insufficient period of commitment from management to PMS. This research indicates that most of the problems associated with PMS are moderately easy to solve. Two other problems that are easy to solve include the problem where there are too many KPIs defined and the problem where there is no organisational member appointed to take ownership of the PMS. According to this research, the top ten ranking problems have high ranking scores and this indicates that they can create major difficulties for the DENC in implementing the performance management system, and the chance of encountering these problems is high in the DENC in comparison to other problems. Almost all the problems ranked in the top ten seem to score highly in terms of the severity of their impact, and therefore this means that these are the problems which have an impact and, when they are not easily solved, they can become a tenacious issue for the organisation.
Keywords: Performance -- Management -- South Africa -- Northern Cape; Northern Cape (South Africa) -- Deptartment of Environment and Nature Conservation; Government productivity -- South Africa -- Northern Cape -- Evaluation; Civil service -- South Africa -- Northern Cape -- Evaluation; Civil service -- South Africa -- Northern Cape -- Management